How to transform workplace bullies into allies - Gilbert, Jacqueline A. (Ethics in practice (Greenwich, Conn.), 2020)
"The rash of bullying incidents within schools, universities, and workplaces has prompted a public outcry and a call to action. To address the growing problem of interpersonal violence, schools have engaged in anti-bullying rallies, businesses have enacted civility policies, states have passed legislation, and efforts have been made to educate individuals on what constitutes good behavior. Increasingly, institutions are realizing from a cost/benefit perspective that a hurtful environment can negatively impact their bottom line. Correspondingly, the rising number of climate surveys to address bullying at work is a testament to the importance of this topic and its potential negative impact. Colleges and universities confirm the need to create a more welcoming culture, as reflected in the current dialogue to promote civility. Publisher offerings in business ethics are inadequate to address this issue, as they focus on the importance of social responsibility and the fallout from moral turpitude. There is a pressing need for materials that will educate students on "civil" concepts and provide them with applied learning. Institutions of higher education would like to inform students about bullying, its ramifications, and how it can be avoided, but a compendium of related exercises is in most cases non-existent. To solidify student learning about positive citizenship, an established author (and anti-bullying activist) has proposed The Courage to Confront Abuse: How to Transform Bullies into Allies. This unique ground-breaking text will provide hands-on, experiential exercises that will engage students with the material, and create a multi-dimensional focus to enable concept retention. Considered a hallmark of applied education, "learning by doing" will be this book's primary emphasis. Exercises will be designed to sharpen critical thinking, immerse students in real world dilemmas, and provide them with tools for conflict resolution. The emotional intelligence promoted by working through in-text scenarios is a sought-after employee trait-one that is desired by both classmates and career centers alike. Unfortunately, people skills at work have long been ignored in traditional college curricula. As a result, schools are creating graduates who possess technical know-how, but not the skill set to effectively navigate personal encounters. The "soft skills" of people savvy which have been deemed crucial to employee success are in large part absent from college offerings. By navigating carefully constructed scenarios, web quests, learning modules, and "teachable moments," readers will develop a keen awareness of what it takes to be a respectful person. Moreover, they will gain expertise in what The Society for Human Resource Management has deemed a critical skill set. Exercises to strengthen incivility awareness are designed not only to prevent potential conflict, but to create change agents within the business arena. Completion of this workbook will provide people with a competitive advantage - and their institution and workplace with a more courteous populace"--